Degradation of Ampicillin Antibiotic by Electrochemical Processes: Evaluation of Antimicrobial Activity of Treated Water - Salazar-Gonzalez, R; Huilinir-Curio, C; Santander-Meyer, R; Vidal-Fuentes, J; Vidal-Fuentes, J (Springer Verlag, 2019)
Ampicillin (AMP) is an antibiotic widely used in hospitals and veterinary clinics around the world for treating infections caused by bacteria. Therefore, it is common to find traces of this antibiotic in wastewater from these entities. In this work, we studied the mineralization of this antibiotic in solution as well as the elimination of its antimicrobial activity by comparing different electrochemical advanced oxidation processes (EAOPs), namely electro-oxidation with hydrogen peroxide (EO-H 2 O 2 ), electro-Fenton (EF), and photo electro-Fenton (PEF). With PEF process, a high degradation, mineralization, and complete elimination of antimicrobial activity were achieved in 120-min electrolysis with high efficiency. In the PEF process, fast mineralization rate is caused by hydroxyl radicals (·OH) that are generated in the bulk, on the anode surface, by UV radiation, and most importantly, by the direct photolysis of complexes formed between Fe 3+ and some organic intermediates. Moreover, some products and intermediates formed during the degradation of the antibiotic Ampicillin, such as inorganic ions, carboxylic acids, and aromatic compounds, were determined by photometric and chromatographic methods. An oxidation pathway is proposed for the complete conversion to CO 2 . © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.